2, 4, 6‐Tri(hydroxy)‐1, 3, 5‐triphosphinine, P3C3(OH)3: The Phosphorus Analogue of Cyanuric Acid. (27th December 2016) - Suter, Riccardo; Mei, Yanbo; Baker, Matthew; Benkő, Zoltan; Li, Zhongshu; Grützmacher, Hansjörg
Abstract: Cyanuric acid (C3 H3 N3 O3 ) is widely used as cross‐linker in basic polymers (often in combination with other crosslinking agents like melamine) but also finds application in more sophisticated materials such as in supramolecular assemblies and molecular sheets. The unknown phosphorus analogue of cyanuric acid, P3 C3 (OH)3, may become an equally useful building block for phosphorus‐based polymers or materials which have unique properties.1 Herein we describe a straightforward synthesis of 2, 4, 6‐tri(hydroxy)‐1, 3, 5‐triphosphinine and its derivatives P3 C3 (OR)3 which have been applied as strong π‐acceptor η 6 ‐ligands in piano stool Mo(CO)3 complexes. Abstract : In drei Fingerschnipsen erledigt : Die Trimerisierung von Boryl‐substituierten Phosphaalkinen ermöglicht die einfache Synthese von Triphosphabenzolen in Gramm‐Mengen. Die Verbindungen bilden stabile Metallkomplexe und können an den Sauerstoffzentren weiter funktionalisiert werden.